Modified acrylic resin and preparation method thereof, transfer coating and transfer film

By using AB two-component modified acrylic resin, the ratio between adamantyl methacrylate, long carbon chain acrylate, vinyl monomer and AB components is regulated, and the temperature resistance, iron resistance and aluminum plating stability of the transfer coating are solved, achieving better performance and application effects.

CN119286334BActive Publication Date: 2025-03-21GUANGZHOU HUMAN CHEM CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411830668.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-21
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

The existing transfer coatings have poor temperature and hot press resistance, and the aluminum-plated layer is prone to corrosion and fall off under humid and heat conditions, which limits its actual production application.

Method used

AB two-component modified acrylic resin is used to optimize the performance of acrylic resin by regulating the ratio between adamantyl methacrylate, long carbon chain acrylate, vinyl monomer and AB components, and improve the temperature resistance, ironing resistance and stability of the aluminum plating layer of the transfer coating.

Benefits of technology

It significantly improves the temperature resistance, hot press resistance and stability of the aluminum-plated layer of transfer coating, solves the problem of corrosion and fall off of the aluminum-plated layer under humid and heat conditions, and is conducive to its actual production and application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_4
    Figure SMS_4
  • Figure SMS_5
    Figure SMS_5
Patent Text Reader

Abstract

The invention relates to the technical field of acrylic resins, and discloses a modified acrylic resin and a preparation method thereof, a transfer coating and a transfer film. The modified acrylic resin comprises an A component and a B component, wherein the weight percentage of the A component is 30 to 70 parts, and the weight percentage of the B component is 30 to 70 parts; wherein the weight percentage of the components in the A component comprises: 20% to 30% adamantyl methacrylate; 10% to 15% long carbon chain acrylate; 5% to 10% hard monomer; 1% to 2% vinyl monomer; and the weight percentage of the components in the B component comprises: 10% to 15% adamantyl methacrylate; 15% to 20% long carbon chain acrylate; 5% to 10% hard monomer; 5% to 10% vinyl monomer. The invention improves the comprehensive performance of the modified acrylic resin, and at the same time solves the problem that the aluminum plating layer is easily corroded and falls off under hot and humid conditions, which is conducive to the practical application of the transfer coating and the transfer film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of acrylic resins, and in particular to a modified acrylic resin and a preparation method thereof, a transfer coating and a transfer film. Background Art

[0002] Transfer coatings are widely used in industries such as leather, wallpaper, ironing cloth, tablecloth, anodized aluminum and cigarette packaging. In practical applications, after coating, aluminizing and laminating, the transfer coating and its carrier can be transferred to another substrate surface. Transfer coatings are mainly composed of acrylic resin, cellulose resin and solvent. Acrylic resin is the key factor affecting the performance of transfer coatings.

[0003] In the prior art, transfer coatings using a single component acrylic resin have some performance defects during actual use. In order to improve the color fastness of the transfer coating to aluminum, the existing solution uses an acrylic resin containing components such as methyl methacrylate, butyl methacrylate, butyl acrylate and methacrylic acid in the transfer coating, but the heat resistance and hot pressing resistance cannot meet the use requirements. In order to improve the flexibility of the transfer coating, the existing solution uses an acrylic resin containing components such as ethylene-vinyl acetate copolymer, ethylene-acrylic acid copolymer and acrylic acid-hydroxyethyl acrylate copolymer in the transfer coating, which will also reduce the temperature resistance of the system. At the same time, when the existing transfer coating is used in the transfer film, the aluminum plating layer is prone to corrosion under hot and humid conditions and falls off the transfer coating, which is not conducive to storage, transportation and long-term use, limiting the application of the transfer coating in actual production. Summary of the invention

[0004] In view of the problems in the prior art that the transfer coating has poor heat resistance and hot pressing resistance and the aluminum plating layer is easily corroded and falls off under hot and humid conditions, the present invention provides a modified acrylic resin and a preparation method thereof, a transfer coating and a transfer film.

[0005] In a first aspect, the present invention provides a modified acrylic resin, comprising a component A and a component B, wherein the weight portion of the component A is 30 to 70 parts, and the weight portion of the component B is 30 to 70 parts;

[0006] Wherein, the A component includes the following components in weight percentage:

[0007] Adamantyl methacrylate 20%~30%;

[0008] Long carbon chain acrylate 10%~15%;

[0009] Hard monomer 5%~10%;

[0010] Vinyl monomer 1%~2%;

[0011] Initiator 0.5%~2%;

[0012] Organic solvent 50%~60%;

[0013] The B component includes the following components in weight percentage:

[0014] Adamantyl methacrylate 10%~15%;

[0015] Long carbon chain acrylate 15%~20%;

[0016] Hard monomer 5%~10%;

[0017] Vinyl monomer 5%~10%;

[0018] Initiator 0.5%~2%;

[0019] Organic solvent 50%~60%.

[0020] In a second aspect, the present invention provides a method for preparing the modified acrylic resin of the first aspect, comprising:

[0021] Obtain adamantyl methacrylate, long carbon chain acrylate, hard monomer and vinyl monomer according to the weight percentage in component A, obtain an initiator according to 75% of the weight percentage in component A, and mix the obtained adamantyl methacrylate, long carbon chain acrylate, hard monomer, vinyl monomer and initiator to obtain a first intermediate composition;

[0022] Obtain an organic solvent according to 80% of the weight percentage in component A, add the obtained organic solvent into a first reaction container, perform nitrogen treatment and heating treatment on the organic solvent during rotation and stirring, and after the reflux of the organic solvent is stable, continuously drop the first intermediate composition into the first reaction container, and keep warm after the dropwise addition is completed to obtain a second intermediate composition; the rotation and stirring speed is 180-240 rpm, the nitrogen gas passing time is 2-5 min, the heating temperature is 73-80° C., the dropwise addition time is 3.5-4.5 h, and the warming time is 1-1.5 h;

[0023] Obtain an initiator according to 25% by weight of component A and an organic solvent according to 20% by weight, and mix the obtained initiator and organic solvent evenly to obtain a third intermediate composition;

[0024] The third intermediate composition is continuously added dropwise to the first reaction container containing the second intermediate composition over a dropwise addition time of 0.5 to 1 hour, and after the dropwise addition is completed, the temperature is raised to 80 to 90° C. and kept warm for 2 to 3 hours, and after the heat preservation is completed, the temperature is lowered to below 60° C. to obtain component A;

[0025] Obtain adamantyl methacrylate, long carbon chain acrylate, hard monomer and vinyl monomer according to the weight percentage in component B, obtain an initiator according to 75% of the weight percentage in component B, and mix the obtained adamantyl methacrylate, long carbon chain acrylate, hard monomer, vinyl monomer and initiator to obtain a fourth intermediate composition;

[0026] An organic solvent is obtained according to 80% of the weight percentage in component B, and the obtained organic solvent is added to a second reaction container. During the process of rotating and stirring the organic solvent, nitrogen treatment and heating treatment are performed, and after the reflux of the organic solvent is stable, the fourth intermediate composition is continuously dripped into the second reaction container, and the temperature is kept after the dripping is completed to obtain a fifth intermediate composition; the rotation and stirring speed is 180-240 rpm, the nitrogen gas flow time is 2-5 min, the heating temperature is 73-80° C., the dripping time is 3.5-4.5 h, and the insulation time is 1-1.5 h;

[0027] Obtain an initiator according to 25% by weight of component B and obtain an organic solvent according to 20% by weight, and mix the obtained initiator and organic solvent evenly to obtain a sixth intermediate composition;

[0028] The sixth intermediate composition is continuously added dropwise to the second reaction container containing the fifth intermediate composition over a dropwise addition time of 0.5 to 1 hour, and after the dropwise addition is completed, the temperature is raised to 80 to 90° C. and kept at this temperature for 2 to 3 hours, and after the keeping of the temperature is completed, the temperature is lowered to below 60° C. to obtain component B;

[0029] 30-70 parts of component A and 30-70 parts of component B are uniformly mixed at 25-35° C. to obtain a modified acrylic resin.

[0030] In a third aspect, the present invention provides a transfer coating, wherein the transfer coating is a coating obtained by mixing a coating solvent, a cellulose resin, an auxiliary agent, and the modified acrylic resin of the first aspect according to a preset component ratio;

[0031] Wherein, the preset component ratio includes:

[0032] The weight portion of the coating solvent is 100-160 parts, the weight portion of the cellulose resin is 50-70 parts, the weight portion of the auxiliary agent is 1-5 parts, and the weight portion of the modified acrylic resin is 60-140 parts;

[0033] The coating solvent includes one or both of ethyl acetate and butanone, and the auxiliary agent includes at least one of a leveling agent, a plasticizer and an antistatic agent.

[0034] In a fourth aspect, the present invention provides a transfer film, comprising a base film, a release layer, an aluminum plating layer and a glue layer, wherein the release layer is a coating formed by coating the transfer coating of the third aspect.

[0035] The present invention provides a modified acrylic resin and a preparation method thereof, a transfer coating and a transfer film. The modified acrylic resin of the present invention is prepared by using two components AB according to different ratios, and the performance optimization of the acrylic resin is achieved through a simple blending process, so as to prepare a modified acrylic resin with excellent comprehensive performance. In the transfer coating prepared by the present invention using the modified acrylic resin, adamantyl methacrylate can improve the heat resistance and hot pressing resistance of the transfer coating, and long carbon chain acrylate and vinyl monomer can balance the flexibility and peeling performance of the transfer coating. By regulating the ratio between the AB components in the modified acrylic resin, the aluminum plating brightness and color powder compatibility of the transfer coating can be effectively improved. At the same time, the ratio between adamantyl methacrylate, long carbon chain acrylate, vinyl monomer and AB components has good synergy, which can solve the problem that the aluminum plating layer is easily corroded and detached under hot and humid conditions while ensuring other properties. The transfer film of the present invention has excellent peelability, flexibility, temperature resistance, hot pressing resistance, and coating brightness and stability after film transfer, which is conducive to the actual production and application of the transfer coating. DETAILED DESCRIPTION

[0036] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0037] In a first aspect, an embodiment of the present invention discloses a modified acrylic resin, comprising a component A and a component B, wherein the weight portion of the component A is 30 to 70 parts, and the weight portion of the component B is 30 to 70 parts;

[0038] Wherein, the A component includes the following components in weight percentage:

[0039] Adamantyl methacrylate 20%~30%;

[0040] Long carbon chain acrylate 10%~15%;

[0041] Hard monomer 5%~10%;

[0042] Vinyl monomer 1%~2%;

[0043] Initiator 0.5%~2%;

[0044] Organic solvent 50%~60%;

[0045] The B component includes the following components in weight percentage:

[0046] Adamantyl methacrylate 10%~15%;

[0047] Long carbon chain acrylate 15%~20%;

[0048] Hard monomer 5%~10%;

[0049] Vinyl monomer 5%~10%;

[0050] Initiator 0.5%~2%;

[0051] Organic solvent 50%~60%.

[0052] Further, acrylic resin is a resin copolymerized from acrylate and methacrylate monomers, which can be used as a film-forming material for coatings. The modified acrylic resin in the present embodiment is a two-component acrylic resin, including component A and component B. During the use of the modified acrylic resin, the polymer monomers in component A and component B are polymerized under the action of an initiator, and the prepolymer of component A and the prepolymer of component B are prepared respectively, and then the prepolymer of component A and the prepolymer of component B are mixed to finally obtain the modified acrylic resin. In the modified acrylic resin, the weight portion of component A is 30 to 70 parts, and the weight portion of component B is 30 to 70 parts. The prepolymer of component A and the prepolymer of component B are proportioned according to a specific mixing ratio, and can be dissolved in each other and remain stable after mixing, which can ensure that the performance of the modified acrylic resin is optimal, and then improve the performance of the transfer coating made based on the modified acrylic resin. On the one hand, by regulating the mixing ratio between the prepolymers of component AB in the modified acrylic resin, the cross-linked structure and functional group distribution of the acrylic resin can be optimized, and the fluidity and film-forming property of the acrylic resin are affected. During the construction of the transfer coating, a smoother and more uniform aluminum-plated surface can be obtained, thereby improving the brightness and visual effect of the aluminum-plated layer. On the other hand, as a film-forming substance for transfer coatings, the structure and properties of modified acrylic resins have an important influence on the dispersibility of color powders. By adjusting the mixing ratio between the AB component prepolymers in the modified acrylic resin, the molecular structure and polarity of the resin can be optimized, so that the color paste, pigment, color powder, etc. in the transfer coating are fully dispersed without precipitation or agglomeration, thereby improving the dispersibility and compatibility of the color powder.

[0053] The monomer selection of acrylic resin has an important influence on the performance and application of the resin. By reasonably matching different types of monomers, modified acrylic resins with excellent performance can be prepared to meet various application requirements. Component A and component B both include adamantyl methacrylate, long carbon chain acrylate, hard monomer, vinyl monomer, initiator and organic solvent, but the content of each component is different, thereby forming a prepolymer of component A and a prepolymer of component B. According to different functions, the monomers of acrylic resin can be divided into hard monomers, soft monomers and functional monomers, which interact with each other during the copolymerization process to form acrylic resins with specific properties. Among them, the glass transition temperature of the hard monomer is high, which has the effect of improving hardness in acrylic resin; the glass transition temperature of the soft monomer is low, which has the effect of improving flexibility and promoting film formation in acrylic resin; the functional monomer improves the functional properties of acrylic resin by introducing specific groups. In addition to the hard monomer, adamantyl methacrylate and long carbon chain acrylate can be used as functional monomers in the components A and B of this embodiment, and the vinyl monomer can be used as both a soft monomer and a functional monomer.

[0054] Adamantyl methacrylate has an adamantane skeleton and a methacrylate group, and mainly plays a role in structural modification and performance improvement in modified acrylic resins. The introduction of adamantyl methacrylate can significantly improve the thermal stability of acrylic resins. The adamantane skeleton of adamantyl methacrylate has a rigid structure, and this structural characteristic can effectively modify the structure of acrylic resins, so that acrylic resins can remain stable at high temperatures, are not prone to decomposition or aging, and improve the temperature resistance of transfer coatings. The rigid structure of adamantyl methacrylate can also enhance the mechanical properties of acrylic resins and improve the hot pressing resistance of transfer coatings. The methacrylate group in adamantyl methacrylate gives the molecule good reactivity, and the enhanced reactivity makes acrylic resins easier to polymerize.

[0055] The molecular chain of long-chain acrylate has a long-chain structure, which makes its molecular structure relatively soft, thus giving the transfer coating good flexibility. This flexibility enables the transfer coating to better adapt to the deformation and stress changes of the substrate after coating, and is not easy to crack. Long-chain acrylate can also enhance the adhesion between the transfer coating and the substrate, making the transfer coating less likely to fall off after coating. As a functional monomer, the unsaturated double bond of the vinyl monomer can undergo polymerization reaction with other monomers. The modified acrylic resin formed by the polymerization of the vinyl monomer has good wettability and permeability, allowing the transfer coating to more easily penetrate into the tiny pores on the surface of the substrate, forming a tighter bond and improving the stripping performance. That is, long-chain acrylate and vinyl monomer can balance the flexibility and stripping performance of the transfer coating.

[0056] The modified acrylic resin of the present invention is prepared by using two components AB according to a specific ratio, and the mixed ratio of adamantyl methacrylate, long carbon chain acrylate, vinyl monomer and AB component prepolymer has good synergy, so that the transfer coating made based on the modified acrylic resin has excellent temperature resistance, hot pressing resistance, flexibility, peeling property and aluminum plating brightness stability, and can also solve the problem that the aluminum plating layer is prone to corrosion and shedding under hot and humid conditions, which is conducive to the actual production and application of the transfer coating.

[0057] Optionally, the structural formula of the adamantyl methacrylate is as follows:

[0058] ;

[0059] Wherein, R is hydrogen or an alkyl group having 1 to 3 carbon atoms.

[0060] Optionally, the adamantyl methacrylate includes at least one of 2-adamantyl methacrylate, 2-methyl-2-adamantyl methacrylate, 2-ethyl-2-adamantyl methacrylate and 2-isopropyl-2-adamantyl methacrylate.

[0061] Further, it can be seen from the structural formula that the adamantyl methacrylate in this embodiment has an R group in addition to the adamantane skeleton and the methacrylate group. Wherein, the R group is hydrogen or an alkyl group with a carbon number of 1 to 3. Preferably, when the R group is hydrogen, the adamantyl methacrylate is 2-adamantyl methacrylate; when the R group is an alkyl group with a carbon number of 1, the adamantyl methacrylate is 2-methyl-2-adamantyl methacrylate; when the R group is an alkyl group with a carbon number of 2, the adamantyl methacrylate is 2-ethyl-2-adamantyl methacrylate; when the R group is an alkyl group with a carbon number of 3, the adamantyl methacrylate is 2-isopropyl-2-adamantyl methacrylate.

[0062] Specifically, when the adamantyl methacrylate is 2-isopropyl-2-adamantyl methacrylate, 2-isopropyl-2-adamantyl methacrylate is a complex compound composed of an adamantane skeleton, an isopropyl group and a methacrylate group. The rigid structure of the adamantane skeleton can improve the thermal stability of the modified acrylic resin, and the isopropyl group and the methacrylate group respectively give the molecule good hydrophobicity and reactivity. The improvement of hydrophobicity enables the acrylic resin to maintain good performance in a humid environment, and the enhancement of reactivity makes the acrylic resin easier to polymerize. The unique chemical structure of 2-isopropyl-2-adamantyl methacrylate makes it an ideal material modifier. Through copolymerization or cross-linking reactions with other monomers, the thermal stability, hydrophobicity and reactivity of the modified acrylic resin can be significantly improved.

[0063] Optionally, the long carbon chain acrylate includes at least one of tetradecyl acrylate, pentadecyl acrylate, hexadecyl acrylate, heptadecanyl acrylate, octadecyl acrylate, tetradecyl methacrylate, pentadecyl methacrylate, hexadecyl methacrylate, heptadecanyl methacrylate and octadecyl methacrylate; and / or,

[0064] The hard monomer includes at least one of acrylate and methacrylate having a glass transition temperature of 50 to 110°C.

[0065] Furthermore, the acrylate compound can be an acrylate or a methacrylate. Long-chain acrylate refers to a structure in which the hydrocarbon chain connected to the ester group in the acrylate compound has a relatively long chain length. The carbon chain length of the long-chain acrylate has a significant effect on the performance and application of acrylic resin in transfer coatings. Too long a carbon chain length will reduce the surface tension and polarity of the transfer coating, resulting in poor compatibility between the coating components, which will affect the uniformity and stability of the coating. At the same time, acrylic resins with too long a carbon chain length will increase the viscosity of the transfer coating, affecting the construction performance and leveling of the transfer coating. Preferably, the long-chain acrylate is selected from one or more of tetradecyl acrylate to octadecyl acrylate and tetradecyl methacrylate to octadecyl methacrylate, that is, the carbon chain length is 14 to 18.

[0066] Similarly, the hard monomer can be either acrylate or methacrylate. The glass transition temperature of the hard monomer is 0 to 150°C. When the modified acrylic resin is applied to the transfer coating, if the glass transition temperature of the hard monomer is too high, the adhesion of the transfer coating may decrease, especially at low temperatures, the brittleness may increase, and it may easily fall off. If the glass transition temperature of the hard monomer is too low, the use range of the transfer coating in a high temperature environment will be limited. Preferably, the hard monomer is selected from one or more of acrylates and methacrylates with a glass transition temperature of 50 to 110°C.

[0067] Optionally, the vinyl monomer consists of vinyl acetate and vinyl ester, and the weight ratio of the vinyl acetate to the vinyl ester is 2:1 to 6:1;

[0068] The structural formula of the tert-butyl ester is as follows:

[0069] ;

[0070] Among them, R1 is an alkyl group with 1 to 7 carbon atoms, R2 is an alkyl group with 1 to 7 carbon atoms, and the sum of the carbon numbers of R1 and R2 is 4 to 8.

[0071] Further, in the present embodiment, a combination of vinyl acetate and tert-butyl vinyl carbonate is used as the vinyl monomer of component A and component B in the modified acrylic resin. Vinyl acetate can be used as a functional monomer to give the modified acrylic resin good weather resistance and rheological properties. Tert-butyl vinyl carbonate can be used as a soft monomer. When tert-butyl vinyl carbonate is added to the modified acrylic resin, it can undergo polymerization reaction with other monomers in the acrylic resin, thereby increasing the flexibility of the coating molecule. At the same time, since tert-butyl vinyl carbonate has a special chemical structure and properties, it can be used as a functional monomer, and the addition of tert-butyl vinyl carbonate can improve the stripping performance of the acrylic resin. As can be seen from the structural formula, tert-butyl vinyl carbonate has a special tertiary carbon structure, and the molecular structure contains an alkyl group on the α-carbon atom, which has a great steric hindrance effect and shielding effect. When the modified acrylic resin is applied to the transfer coating, the steric hindrance effect in the molecular structure of tert-butyl vinyl carbonate enables the transfer coating to better maintain the stability of the structure when subjected to external forces, and is not prone to cracking and peeling, thereby improving the adhesion and durability of the coating. The steric effect in the molecular structure of tert-butyl vinyl carbonate significantly improves the thermal stability, solvent resistance, water resistance and gloss of the transfer coating. In addition, the flexible alkyl substituents of tert-butyl vinyl carbonate can reduce the interaction between polymer segments, thereby improving the stripping performance of the coating.

[0072] When vinyl acetate and tert-butyl vinyl carbonate are used in combination in this embodiment, the weight ratio of vinyl acetate to tert-butyl vinyl carbonate is limited to a range of 2 to 6. If the weight ratio is too small, the highly branched structure of tert-butyl vinyl carbonate in the modified acrylic resin may limit the mobility of the molecule, thereby reducing the flexibility. At the same time, the steric hindrance effect and shielding effect are too strong, which affects the stripping performance. If the weight ratio is too large, the modified acrylic resin may lack sufficient tert-butyl vinyl carbonate to provide the necessary strength and stability, affecting the performance of the coating.

[0073] In addition, in the structural formula of versatate vinyl carbonate, R1 is an alkyl group having 1 to 7 carbon atoms, R2 is an alkyl group having 1 to 7 carbon atoms, and the sum of the carbon atoms of R1 and R2 is 4 to 8, that is, the sum of the carbon atoms of R1 and R2 is 4, 5, 6, 7 or 8.

[0074] Optionally, the versatate vinyl carbonate includes at least one of VeoVa9, VeoVa10 and VeoVa11.

[0075] Furthermore, the versatate vinyl carbonate is preferably selected from one or more of VeoVa9, VeoVa10 and VeoVa11. Among them, VeoVa9 is also called neononanoic acid vinyl ester, with a total carbon atom count of 9, and the corresponding sum of the carbon atoms of R1 and R2 is 4. VeoVa10 is also called neodecanoic acid vinyl ester, with a total carbon atom count of 10, and the corresponding sum of the carbon atoms of R1 and R2 is 5. VeoVa11 is also called neoundecanoic acid vinyl ester, with a total carbon atom count of 11, and the corresponding sum of the carbon atoms of R1 and R2 is 6.

[0076] Optionally, the initiator includes one or both of azobisisobutyronitrile and azobisisoheptanenitrile; and / or,

[0077] The organic solvent includes at least one of ethyl acetate, n-propyl acetate, n-butyl acetate and butanone.

[0078] Further, initiator is a substance used to initiate a chain reaction in a chemical reaction. In modified acrylic resin, initiator can initiate copolymerization through free radicals, prompting monomer molecules to react to form a linear or cross-linked polymer structure. Initiator includes two types of peroxide initiators and azo initiators. Peroxide initiators (benzoyl peroxide, tert-butyl perbenzoate and tert-butyl peroxide-2-ethylhexanoate) are free radical initiators, and azo initiators (azobisisobutyronitrile, azobisisoheptanitrile) are free radical initiators with multifunctional groups, which can be used for the copolymerization of modified acrylic resin. In the present embodiment, the initiator is preferably selected from one or both of azobisisobutyronitrile and azobisisoheptanitrile.

[0079] In modified acrylic resin, the role of organic solvent is to act as a reaction medium and carrier, control the reaction speed and molecular weight, improve the solubility and stability of the resin, and enable the monomer, initiator and other additives to be evenly mixed, and then the polymerization reaction occurs. Ethyl acetate, n-propyl acetate, n-butyl acetate and butanone have excellent solubility properties and can be used as organic solvents for modified acrylic resin.

[0080] In a second aspect, an embodiment of the present invention further discloses a method for preparing the modified acrylic resin of the first aspect, comprising:

[0081] Obtain adamantyl methacrylate, long carbon chain acrylate, hard monomer and vinyl monomer according to the weight percentage in component A, obtain an initiator according to 75% of the weight percentage in component A, and mix the obtained adamantyl methacrylate, long carbon chain acrylate, hard monomer, vinyl monomer and initiator to obtain a first intermediate composition;

[0082] Obtain an organic solvent according to 80% of the weight percentage in component A, add the obtained organic solvent into a first reaction container, perform nitrogen treatment and heating treatment on the organic solvent during rotation and stirring, and after the reflux of the organic solvent is stable, continuously drop the first intermediate composition into the first reaction container, and keep warm after the dropwise addition is completed to obtain a second intermediate composition; the rotation and stirring speed is 180-240 rpm, the nitrogen gas passing time is 2-5 min, the heating temperature is 73-80° C., the dropwise addition time is 3.5-4.5 h, and the warming time is 1-1.5 h;

[0083] Obtain an initiator according to 25% by weight of component A and an organic solvent according to 20% by weight, and mix the obtained initiator and organic solvent evenly to obtain a third intermediate composition;

[0084] The third intermediate composition is continuously added dropwise to the first reaction container containing the second intermediate composition over a dropwise addition time of 0.5 to 1 hour, and after the dropwise addition is completed, the temperature is raised to 80 to 90° C. and kept warm for 2 to 3 hours, and after the heat preservation is completed, the temperature is lowered to below 60° C. to obtain component A;

[0085] Obtain adamantyl methacrylate, long carbon chain acrylate, hard monomer and vinyl monomer according to the weight percentage in component B, obtain an initiator according to 75% of the weight percentage in component B, and mix the obtained adamantyl methacrylate, long carbon chain acrylate, hard monomer, vinyl monomer and initiator to obtain a fourth intermediate composition;

[0086] An organic solvent is obtained according to 80% of the weight percentage in component B, and the obtained organic solvent is added to a second reaction container. During the process of rotating and stirring the organic solvent, nitrogen treatment and heating treatment are performed, and after the reflux of the organic solvent is stable, the fourth intermediate composition is continuously dripped into the second reaction container, and the temperature is kept after the dripping is completed to obtain a fifth intermediate composition; the rotation and stirring speed is 180-240 rpm, the nitrogen gas flow time is 2-5 min, the heating temperature is 73-80° C., the dripping time is 3.5-4.5 h, and the insulation time is 1-1.5 h;

[0087] Obtain an initiator according to 25% by weight of component B and obtain an organic solvent according to 20% by weight, and mix the obtained initiator and organic solvent evenly to obtain a sixth intermediate composition;

[0088] The sixth intermediate composition is continuously added dropwise to the second reaction container containing the fifth intermediate composition over a dropwise addition time of 0.5 to 1 hour, and after the dropwise addition is completed, the temperature is raised to 80 to 90° C. and kept at this temperature for 2 to 3 hours, and after the keeping of the temperature is completed, the temperature is lowered to below 60° C. to obtain component B;

[0089] 30-70 parts of component A and 30-70 parts of component B are uniformly mixed at 25-35° C. to obtain a modified acrylic resin.

[0090] Further, in this embodiment, the polymer monomers of each component A and component B are first polymerized under the action of an initiator to prepare a prepolymer of component A and a prepolymer of component B, respectively, and then the prepolymer of component A and the prepolymer of component B are mixed to finally obtain a modified acrylic resin. Form prepolymers of components A and B. The preparation process of the prepolymer of component A and the prepolymer of component B are similar. This embodiment describes the specific process of preparing the prepolymer of component A, and the prepolymer of component B is not repeated. First, the adamantyl methacrylate, long carbon chain acrylate, hard monomer, vinyl monomer and most (75%) initiator except the organic solvent are mixed uniformly according to the weight percentage of component A to obtain a first intermediate composition, so as to achieve premixing of various monomers and initiators. Secondly, add most (80%) organic solvents to the reaction vessel, rotate and stir at a speed of 180 to 240 revolutions per minute, and continue to pass nitrogen for 2 to 5 minutes to remove the air in the organic solvent and raise the temperature to 73 to 80 ° C to provide suitable temperature conditions for the copolymerization reaction. After confirming that the reflux is stable, the first intermediate composition is continuously and uniformly added to the reaction vessel within 3.5 to 4.5 hours, and the reaction vessel is kept warm for 1 to 1.5 hours to obtain the second intermediate composition, which is conducive to controlling the reaction rate and allowing various monomers to fully undergo polymerization reactions in the organic solvent. Again, the remaining small portion (20%) of the organic solvent and the small portion (25%) of the initiator are mixed evenly to obtain the third intermediate composition, and the third intermediate composition is uniformly added to the reaction vessel containing the second intermediate composition within 0.5 to 1 hour. After the addition is completed, the temperature is raised to 80 to 90°C and kept warm for 2 to 3 hours. The organic solvent and initiator are added twice, the second addition amount is less than the first addition amount, and the temperature is kept at a higher temperature, which helps to further polymerize the unreacted monomers. Finally, after the insulation is completed, it is cooled to below 60°C to obtain a modified acrylic resin.

[0091] In a third aspect, an embodiment of the present invention further discloses a transfer coating, wherein the transfer coating is a coating obtained by mixing a coating solvent, a cellulose resin, an auxiliary agent, and the modified acrylic resin of the first aspect according to a preset component ratio;

[0092] Wherein, the preset component ratio includes:

[0093] The weight portion of the coating solvent is 100-160 parts, the weight portion of the cellulose resin is 50-70 parts, the weight portion of the auxiliary agent is 1-5 parts, and the weight portion of the modified acrylic resin is 60-140 parts;

[0094] The coating solvent includes one or both of ethyl acetate and butanone, and the auxiliary agent includes at least one of a leveling agent, a plasticizer and an antistatic agent.

[0095] Furthermore, modified acrylic resin is the main film-forming substance of transfer coating. Cellulose resin can increase the viscosity of transfer coating, making it easier to apply and control, and can also be used as an accelerator to promote the curing of the coating as soon as possible. Additives are some compounds added to improve the processing properties of the coating or its own performance is insufficient, such as leveling agents for improving leveling and uniformity, plasticizers for reducing the viscosity of polymer melts, and antistatic agents for reducing static electricity accumulation.

[0096] In another embodiment, dye powder or nano pigment color paste can be added to the transfer coating as needed to give the transfer coating product different colors. In this case, the cellulose resin can increase the compatibility of the coating with the dye, prevent the dye from precipitating from the coating, and improve the color fastness to make the coating have a good color brightness.

[0097] In a fourth aspect, an embodiment of the present invention further discloses a transfer film, which includes a base film, a release layer, an aluminum plating layer and a glue layer, wherein the release layer is a coating formed by coating the transfer coating of the third aspect.

[0098] Furthermore, in one embodiment, the manufacturing method of the transfer film includes: using polyester resin as the base film of the transfer film; obtaining a release agent, uniformly coating the transfer coating of the third aspect on the base film and performing a drying and curing treatment to obtain a release layer of the transfer film; performing a vacuum aluminum plating operation on the release layer to obtain an aluminum plating layer of the transfer film; obtaining transfer hot stamping glue, uniformly coating the transfer hot stamping glue on the aluminum plating layer and performing a drying treatment to obtain a glue layer of the leather transfer film. In the subsequent practical application of the transfer film, the base film, the release layer, the aluminum plating layer film and the glue layer are transferred to the surface of a substrate such as leather, wallpaper, ironing cloth or tablecloth and subjected to a hot pressing treatment, and then the base film is peeled off from the release layer to obtain a transfer product (such as transfer leather). Among them, the polyester resin (PET) film has the characteristics of high tensile strength, good thermal stability, low thermal shrinkage, smooth and clean surface and good peelability, and can be used as the base film of the transfer film, and the base film is a carrier for vacuum aluminum plating. When the transfer coating is evenly applied on the base film and then dried, the drying temperature is 160~200℃ and the drying time is 15~25 seconds. When the transfer hot stamping glue is evenly applied on the aluminum layer and then dried, the drying temperature is 120~160℃ and the drying time is 10~20 seconds. When the transfer film and the base material are heat-pressed, the heat-pressing temperature is 100~130℃ and the heat-pressing time is 5~8 minutes.

[0099] Specific examples and comparative examples are as follows:

[0100] Example 1

[0101] Preparation of modified acrylic resin:

[0102] 2-adamantyl methacrylate is used as the adamantyl methacrylate of component A, hexadecyl acrylate is used as the long carbon chain acrylate of component A, methyl methacrylate is used as the hard monomer of component A, vinyl acetate and VeoVa10 are used as the vinyl monomers of component A, azobisisoheptonitrile is used as the initiator of component A, and n-propyl acetate is used as the organic solvent of component A. 2-adamantyl methacrylate, hexadecyl acrylate, methyl methacrylate, vinyl acetate, VeoVa10 and 75% of the total amount of azobisisoheptanenitrile as initiator are uniformly mixed to obtain a first intermediate composition; 80% of the total amount of organic solvent, n-propyl acetate, is added to the first reaction container, the rotation speed is adjusted to 180 rpm, nitrogen is passed for 3 minutes, the temperature is raised to 75°C, and after the reflux is stable, the first intermediate composition is added dropwise for 4 hours, and then the mixture is kept warm for 1.5 hours to obtain a second intermediate composition; the remaining 20% ​​of the total amount of organic solvent, n-propyl acetate and 25% of the total amount of azobisisoheptanenitrile as initiator are uniformly mixed to obtain a third intermediate composition; the third intermediate composition is added dropwise to the second intermediate composition for 0.5 hours, the temperature is then raised to 80°C and kept warm for 2 hours, and then the temperature is lowered to below 60°C to discharge the material, to obtain component A of Example 1.

[0103] 2-adamantyl methacrylate is used as the adamantyl methacrylate of component B, hexadecyl acrylate is used as the long carbon chain acrylate of component B, isobutyl methacrylate is used as the hard monomer of component B, vinyl acetate and VeoVa10 are used as the vinyl monomers of component B, azobisisoheptonitrile is used as the initiator of component B, and butanone is used as the organic solvent of component B. 2-adamantyl methacrylate, hexadecyl acrylate, isobutyl methacrylate, vinyl acetate, VeoVa10 and 75% of the total amount of azobisisoheptanenitrile as initiator are uniformly mixed to obtain a fourth intermediate composition; 80% of the total amount of organic solvent, butanone, is added to the first reaction container, the rotation speed is adjusted to 180 rpm, nitrogen is passed for 3 minutes, the temperature is raised to 75°C, and after the reflux is stable, the fourth intermediate composition is added dropwise for 4 hours, and then the mixture is kept warm for 1 hour to obtain a fifth intermediate composition; the remaining 20% ​​of the total amount of organic solvent, butanone and 25% of the total amount of azobisisoheptanenitrile as initiator are uniformly mixed to obtain a sixth intermediate composition; the sixth intermediate composition is added dropwise to the fifth intermediate composition for 1 hour, the temperature is then raised to 80°C and kept warm for 2.5 hours, and then the temperature is lowered to below 60°C to obtain component B of Example 1.

[0104] 40 parts of component A and 60 parts of component B were mixed uniformly at 25° C. to obtain the modified acrylic resin of Example 1.

[0105] Preparation of transfer coating:

[0106] 137 parts of coating solvent (methyl ethyl ketone), 60 parts of cellulose resin, 3 parts of auxiliary agent and 100 parts of modified acrylic resin were mixed to obtain the transfer coating of Example 1.

[0107] Furthermore, on the basis of Example 1, the present invention adjusts the component types and contents of adamantyl methacrylate, long carbon chain acrylate, hard monomer, vinyl monomer, initiator and organic solvent, and also adjusts the ratio between component A and component B, and respectively provides Examples 2 to 5 and Comparative Examples 1 to 8. Among them, the other preparation processes of the modified acrylic resin and transfer coating in Examples 2 to 5 and Comparative Examples 1 to 8 are consistent with those in Example 1.

[0108] Specifically, the weight percentage components of component A in the embodiments and comparative examples are shown in Table 1 below.

[0109] Table 1 Weight percentage of component A in the examples and comparative examples

[0110]

[0111] It can be seen from Table 1 that compared with component A in Example 1, the vinyl monomer in Comparative Example 1 is styrene; the adamantyl methacrylate in Comparative Example 2 is 1-adamantyl methacrylate; the weight ratio between vinyl acetate and VeoVa10 in Comparative Example 3 is 1:1; the hard monomer in Comparative Example 4 is methacrylic acid; the long carbon chain acrylate in Comparative Example 5 is lauric acrylate; the weight percentages of adamantyl methacrylate, long carbon chain acrylate and hard monomer in Comparative Example 6 exceed the corresponding ranges; Comparative Example 7 contains only component A; and Comparative Example 8 does not contain component A.

[0112] Specifically, the weight percentage of component B in the embodiments and comparative examples is shown in Table 2 below.

[0113] Table 2 Weight percentage of component B in the examples and comparative examples

[0114]

[0115] It can be seen from Table 2 that compared with component B in Example 1, the vinyl monomer in Comparative Example 1 is styrene; the adamantyl methacrylate in Comparative Example 2 is 1-adamantyl methacrylate; the weight ratio between vinyl acetate and VeoVa10 in Comparative Example 3 is 1:1; the hard monomer in Comparative Example 4 is methacrylic acid; the long carbon chain acrylate in Comparative Example 5 is lauric acrylate; the weight percentages of adamantyl methacrylate, long carbon chain acrylate and hard monomer in Comparative Example 6 exceed the corresponding ranges; Comparative Example 7 does not contain component B; and Comparative Example 8 only contains component B.

[0116] Specifically, the components by weight of the transfer coating in the examples and comparative examples are shown in Table 3 below.

[0117] Table 3 Components by weight of transfer coatings in Examples and Comparative Examples

[0118]

[0119] It can be seen from Table 3 that compared with the transfer coating in Example 1, Comparative Example 7 contains only component A but not component B, and Comparative Example 8 contains only component B but not component A. The total weight of the transfer coatings in Examples 1 to 5 and Comparative Examples 1 to 8 is equal, such as 30 kg.

[0120] The transfer coatings prepared in Examples 1 to 5 and Comparative Examples 1 to 8 were tested for flexibility, peelability, aluminum plating brightness, hot pressing resistance, solvent resistance, aluminum color fastness, thermal stability, wet heat corrosion resistance, and color powder / color paste compatibility.

[0121] Flexibility test: The transfer coatings of the embodiments and comparative examples were coated on a coating machine with a 150-mesh steel roller, and the coatings were pulled apart with 3M tape to observe the flexibility of the coatings. The flexibility was evaluated at three levels: A, B, and C. Among them, A means excellent flexibility, and the coating has excellent toughness after pulling apart; B means average flexibility, and the coating has certain toughness after pulling apart; C means slightly poor flexibility, and the coating has slightly poor toughness and good edge cutting after pulling apart.

[0122] Peelability test: The transfer coatings of the embodiment and the comparative example were tested on a tape peeling force tester PT-501C to observe the peeling state and peeling strength. The following three levels of evaluation were performed according to the peeling state and peeling strength. Among them, A means excellent peeling, smooth peeling without jamming, and peeling strength of 9~10gf / cm; B means good peeling, smooth peeling without jamming, and peeling strength of 10~11gf / cm; C means average peeling, there is jamming in peeling, and the peeling strength is unstable.

[0123] Aluminum plating brightness test: The transfer coatings of the embodiment and the comparative example were coated on a coater with a 150 mesh steel roller and then vacuum aluminum-plated. The glossiness of the aluminum-plated film was tested with a colorimeter, and the three grades of A, B, and C were evaluated according to the test results of the colorimeter. Among them, A means that the aluminum plating brightness is excellent, and the brightness tested by the colorimeter is greater than 95; B means that the aluminum plating brightness is good, and the brightness tested by the colorimeter is 90-95; C means that the aluminum plating brightness is average, and the brightness tested by the colorimeter is less than 90.

[0124] Hot pressing resistance test: The transfer coatings of the examples and comparative examples were coated on a coating machine with a 150-mesh steel roller and then vacuum-coated with aluminum. The aluminum-coated film was then transferred to the cardboard substrate, and then hot-pressed for 4 seconds under a pressure of 4kg using a heat sealer. Different hot pressing temperatures were set from low to high until whitening occurred after hot pressing. Four grades of A, B, C, and D were evaluated according to the hot pressing temperature. Among them, A means excellent hot pressing resistance, and the hot pressing temperature is greater than 180°C; B means good hot pressing resistance, and the hot pressing temperature is 150~180°C; C means average hot pressing resistance, and the hot pressing temperature is 130~150°C; D means poor hot pressing resistance, and the hot pressing temperature is less than 130°C.

[0125] Solvent resistance test: The transfer coatings of the examples and comparative examples were coated on a coating machine with a 150-mesh steel roller and then vacuum-coated with aluminum. The aluminum-coated film was then transferred to the cardboard substrate. After that, it was thoroughly wetted with a mixed solvent of alcohol and ethyl acetate in a weight ratio of 1:1 on a 1kg standard weight wrapped with a dust-free cloth. It was placed horizontally and pushed and pulled back and forth with force to examine the number of wipes when the coating was just damaged. Four grades of A, B, C, and D were evaluated according to the number of wipes. Among them, A means excellent solvent resistance, with a wipe number of more than 300 times; B means good solvent resistance, with a wipe number of 200 to 300 times; C means average solvent resistance, with a wipe number of 100 to 200 times; D means poor solvent resistance, with a wipe number of less than 100 times.

[0126] Color aluminum fastness: The aluminum transfer coatings of the embodiment and the comparative example were coated with a 150 mesh steel roller on a coating machine and then vacuum aluminum-plated. The aluminum-plated film was then transferred to the leather substrate. The leather was rubbed by hand. After obvious wrinkles were found on all positions of the leather surface, it was torn off 5 times with 3M tape. The 10x10cm leather surface was observed with the naked eye to see if there were aluminum spots falling off. Four grades of A, B, C, and D were evaluated according to the number of aluminum spots falling off. Among them, A means excellent color aluminum fastness, with 0 aluminum spots falling off; B means good color aluminum fastness, with 1 to 3 aluminum spots falling off; C means average color aluminum fastness, with 3 to 5 aluminum spots falling off; D means poor color aluminum fastness, with more than 5 aluminum spots falling off.

[0127] Thermal stability test: The transfer coatings of the examples and comparative examples were coated on a coating machine with a 150-mesh steel roller, and the coated films were vacuum-aluminized; the aluminized films were placed in an oven at different temperatures for 30 minutes to observe whether there was a whitening phenomenon. The whitening temperature point is its temperature resistance point.

[0128] Wet heat corrosion resistance test: The transfer coatings of the examples and comparative examples were coated on a coating machine with a 150-mesh steel roller, and the coated film was vacuum-aluminized; the aluminized film was placed in an environment of 60°C and 85% RH for 1200 hours, and the appearance was observed to see if there was corrosion or shedding. Four grades of A, B, C, and D were evaluated according to the area of ​​corrosion shedding. Among them, A means excellent wet heat corrosion resistance and no shedding; B means good wet heat corrosion resistance and a shedding area of ​​less than 1%; C means average wet heat corrosion resistance and a shedding area of ​​less than 5%; D means poor wet heat corrosion resistance and a shedding area of ​​more than 5%.

[0129] Toner / color paste compatibility test: Add toner / color paste to the transfer coating of the embodiment and the comparative example in a certain proportion, stir evenly, filter, and observe the residue. The residue residue is evaluated according to the following four levels, where A indicates excellent compatibility of toner / color paste, with no residue residue; B indicates good compatibility of toner / color paste, with only a small amount of residue residue; C indicates general compatibility of toner / color paste, with a small amount of residue residue; and D indicates poor compatibility of toner / color paste, with a large amount of residue residue.

[0130] The test results of transfer coating performance in the examples and comparative examples are shown in Table 4 below.

[0131] Table 4 Performance test results of the embodiments and comparative examples

[0132]

[0133] From the test results in Table 4, it can be seen that there are differences in the evaluation grades between Examples 1 to 5 due to the different types of components corresponding to various monomers and the changes in the weight ratios between the components. However, compared with the comparative examples, the examples have better comprehensive performance in terms of flexibility, peelability, aluminum plating brightness, hot pressing resistance, solvent resistance, color aluminum fastness, thermal stability, wet heat corrosion resistance, and color powder / color paste compatibility of the transfer coating. Comparing Comparative Example 1 with Example 1, since the vinyl monomer in Comparative Example 1 is styrene, rather than a combination of vinyl acetate and versatate, the flexibility, peelability and aluminum plating brightness of the transfer coating are reduced. Comparing Comparative Example 2 with Example 1, since the adamantyl methacrylate in Comparative Example 2 is 1-adamantyl methacrylate, the position of the R group does not meet the requirements, resulting in a decrease in the aluminum plating brightness, hot pressing resistance, color aluminum fastness, thermal stability and wet heat corrosion resistance of the transfer coating. Comparative Example 3 is compared with Example 1. Since the weight ratio between vinyl acetate and VeoVa10 in Comparative Example 3 is 1:1, the weight ratio is too small, resulting in a decrease in the flexibility and wet heat corrosion resistance of the transfer coating. Comparative Example 4 is compared with Example 1. Since the hard monomer in Comparative Example 4 is methacrylic acid, the glass transition temperature does not meet the requirements, resulting in a decrease in the peelability, color aluminum fastness and wet heat corrosion resistance of the transfer coating. Comparative Example 5 is compared with Example 1. Since the long carbon chain acrylate in Comparative Example 5 is lauric acrylate, the flexibility, peelability and wet heat corrosion resistance of the transfer coating are decreased. Comparative Example 6 is compared with Example 1. Since the weight percentages of adamantyl methacrylate, long carbon chain acrylate and hard monomer in Comparative Example 6 do not meet the requirements, the aluminum plating brightness, hot pressing resistance, solvent resistance, color aluminum fastness, thermal stability and wet heat corrosion resistance of the transfer coating are decreased. Comparing Comparative Examples 7 and 8 with Example 1, Comparative Example 7 contains only component A, and has insufficient performance in terms of flexibility, peelability, color fastness to aluminum, and color powder / color paste compatibility. Comparative Example 8 contains only component B, and has insufficient performance in terms of aluminum plating brightness, hot pressing resistance, solvent resistance, and temperature resistance. Example 1, on the basis of adding adamantyl methacrylate, long carbon chain acrylate, hard monomer, and vinyl monomer, uses component A and component B in combination, and has excellent comprehensive performance.

[0134] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A modified acrylic resin, characterized in that: Comprising component A and component B, wherein the weight portion of component A is 30 to 70 parts, and the weight portion of component B is 30 to 70 parts; Wherein, the A component includes the following components in weight percentage: Adamantyl methacrylate 20%~30%; Long carbon chain acrylate 10%~15%; Hard monomer 5%~10%; Vinyl monomer 1%~2%; Initiator 0.5%~2%; Organic solvent 50%~60%; The B component includes the following components in weight percentage: Adamantyl methacrylate 10%~15%; Long carbon chain acrylate 15%~20%; Hard monomer 5%~10%; Vinyl monomer 5%~10%; Initiator 0.5%~2%; Organic solvent 50%~60%; The structural formula of the adamantyl methacrylate is as follows: , and R is hydrogen or an alkyl group having 1 to 3 carbon atoms; The carbon chain length of the long carbon chain acrylate is 14 to 18; The hard monomer includes at least one of acrylate and methacrylate having a glass transition temperature of 50 to 110°C; The vinyl monomer is composed of vinyl acetate and versatate vinyl carbonate, and the structural formula of versatate vinyl carbonate is as follows: , R1 is an alkyl group having 1 to 7 carbon atoms, R2 is an alkyl group having 1 to 7 carbon atoms, and the sum of the carbon numbers of R1 and R2 is 4 to 8.

2. The modified acrylic resin according to claim 1, characterized in that The adamantyl methacrylate includes at least one of 2-adamantyl methacrylate, 2-methyl-2-adamantyl methacrylate, 2-ethyl-2-adamantyl methacrylate, and 2-isopropyl-2-adamantyl methacrylate.

3. The modified acrylic resin according to claim 1, characterized in that The long carbon chain acrylic acid ester includes at least one of tetradecyl acrylate, pentadecyl acrylate, hexadecyl acrylate, heptadecanyl acrylate, octadecyl acrylate, tetradecyl methacrylate, pentadecyl methacrylate, hexadecyl methacrylate, heptadecanyl methacrylate and octadecyl methacrylate.

4. The modified acrylic resin according to claim 1, characterized in that The weight ratio of the vinyl acetate to the versatate vinyl carbonate is 2:1 to 6:

1.

5. The modified acrylic resin according to claim 1, characterized in that The versatate vinyl carbonate includes at least one of VeoVa9, VeoVa10 and VeoVa11.

6. The modified acrylic resin according to claim 1, characterized in that The initiator comprises one or both of azobisisobutyronitrile and azobisisoheptanenitrile; and / or, The organic solvent includes at least one of ethyl acetate, n-propyl acetate, n-butyl acetate and butanone.

7. A method for preparing a modified acrylic resin according to any one of claims 1 to 6, characterized in that: include: Obtain adamantyl methacrylate, long carbon chain acrylate, hard monomer and vinyl monomer according to the weight percentage in component A, obtain an initiator according to 75% of the weight percentage in component A, and mix the obtained adamantyl methacrylate, long carbon chain acrylate, hard monomer, vinyl monomer and initiator to obtain a first intermediate composition; Obtain an organic solvent according to 80% of the weight percentage in component A, add the obtained organic solvent into a first reaction container, perform nitrogen treatment and heating treatment on the organic solvent during rotation and stirring, and after the reflux of the organic solvent is stable, continuously drop the first intermediate composition into the first reaction container, and keep warm after the dropwise addition is completed to obtain a second intermediate composition; the rotation and stirring speed is 180-240 rpm, the nitrogen gas passing time is 2-5 min, the heating temperature is 73-80° C., the dropwise addition time is 3.5-4.5 h, and the warming time is 1-1.5 h; Obtain an initiator according to 25% by weight of component A and an organic solvent according to 20% by weight, and mix the obtained initiator and organic solvent evenly to obtain a third intermediate composition; The third intermediate composition is continuously added dropwise to the first reaction container containing the second intermediate composition over a dropwise addition time of 0.5 to 1 hour, and after the dropwise addition is completed, the temperature is raised to 80 to 90° C. and kept warm for 2 to 3 hours, and after the heat preservation is completed, the temperature is lowered to below 60° C. to obtain component A; Obtain adamantyl methacrylate, long carbon chain acrylate, hard monomer and vinyl monomer according to the weight percentage in component B, obtain an initiator according to 75% of the weight percentage in component B, and mix the obtained adamantyl methacrylate, long carbon chain acrylate, hard monomer, vinyl monomer and initiator to obtain a fourth intermediate composition; An organic solvent is obtained according to 80% of the weight percentage in component B, and the obtained organic solvent is added to a second reaction container. During the process of rotating and stirring the organic solvent, nitrogen treatment and heating treatment are performed, and after the reflux of the organic solvent is stable, the fourth intermediate composition is continuously dripped into the second reaction container, and the temperature is kept after the dripping is completed to obtain a fifth intermediate composition; the rotation and stirring speed is 180-240 rpm, the nitrogen gas flow time is 2-5 min, the heating temperature is 73-80° C., the dripping time is 3.5-4.5 h, and the insulation time is 1-1.5 h; Obtain an initiator according to 25% by weight of component B and obtain an organic solvent according to 20% by weight, and mix the obtained initiator and organic solvent evenly to obtain a sixth intermediate composition; The sixth intermediate composition is continuously added dropwise to the second reaction container containing the fifth intermediate composition over a dropwise addition time of 0.5 to 1 hour, and after the dropwise addition is completed, the temperature is raised to 80 to 90° C. and kept at this temperature for 2 to 3 hours, and after the keeping of the temperature is completed, the temperature is lowered to below 60° C. to obtain component B; 30-70 parts of component A and 30-70 parts of component B are uniformly mixed at 25-35° C. to obtain a modified acrylic resin.

8. A transfer coating, characterized in that: The transfer coating is a coating obtained by mixing a coating solvent, a cellulose resin, an additive, and the modified acrylic resin according to any one of claims 1 to 6 according to a preset component ratio; Wherein, the preset component ratio includes: The weight portion of the coating solvent is 100-160 parts, the weight portion of the cellulose resin is 50-70 parts, the weight portion of the auxiliary agent is 1-5 parts, and the weight portion of the modified acrylic resin is 60-140 parts; The coating solvent includes one or both of ethyl acetate and butanone, and the auxiliary agent includes at least one of a leveling agent, a plasticizer and an antistatic agent.

9. A transfer film, characterized in that: The transfer film comprises a base film, a release layer, an aluminum-plated layer and a glue layer, and the release layer is a coating formed by coating the transfer coating as claimed in claim 8.

Citation Information

Patent Citations

  • Water-based aluminizing transfer coating as well as preparation method and application thereof

    CN113930141A

  • Thermosetting release coating agent, cured product, and thermosetting release film and method for producing same

    CN114075388A